Descemet?s Membrane Detachment Repair with Sodium Hyaluronate after Phacoemulsification - Wasif M. Kadri, Ghulam Hussain Asif (Pakistan Journal of Ophthalmology, 2018)
Purpose: To evaluate the use of sodium hyaluronate in reattachment of detached Descemet’s membrane after phacoemulsification. Material and Methods: Five eyes of five patients with non planar Descemet’s membrane detachment (DMD) during phacoemulsification from 2006 till 2012 are included in this interventional case series. Planar DMD cases were excluded from the study. This study was conducted at DHQ Hospital Vehari. There were four females and one male with the age range of 65 to 75 years with mean age of 70 years. Results: All eyes got reattachment of non planar DMD with intracameral injection of Sodium Hyaluronate. Descemet’s membrane remained attached in all the subsequent visits till 12 months post-operatively. The average time for the corneal decompensation to resolve was 24 to 48 hours. All the patients had raised intra ocular pressure (average 31-35 mm Hg) within the first 24 hours which was managed with a single Mannitol injection and topical beta blockers for one week. In one of the patients intracameral Sodium Hyaluronate (Provisc) had to be repeated after 21 days. Post-operative BCVA of 6/9 to 6/6 was achieved at 6 weeks postoperatively. Conclusion: If Non planar extensive Descemet’s membrane detachment is noted during phacoemulsification then limited manipulation helps in preventing aggravation of the problem. After surgery identifying the degree of DMD and intracameral injection of Sodium Hyaluronate re-attaches the DMD.